Methylmercury formation in biofilms of Geobacter sulfurreducens - Yunda, Elena; Gutensohn, Mareike; Ramstedt, Madeleine; Björn, Erik (Frontiers in Microbiology, 2023)
Mercury (Hg) is a major environmental pollutant that accumulates in biota predominantly in the form of methylmercury (MeHg). Surface-associated microbial communities (biofilms) represent an important source of MeHg in natural aquatic systems. In this work, we report MeHg formation in biofilms of the iron-reducing bacterium Geobacter sulfurreducens. Biofilms were prepared in media with varied nutrient load for three, five or seven days, and their structural properties were characterized using confocal laser scanning microscopy, cryo- scanning electron microscopy and Fourier-transform infrared spectroscopy. Biofilms cultivated for three days with vitamins in the medium had the highest surface coverage, and they also contained abundant extracellular matrix. Using three and seven-days-old biofilms, we demonstrate that G. sulfurreducens biofilms prepared in media with various nutrient load produce MeHg, of which a significant portion is released to the surrounding medium. The Hg methylation rate constant determined in 6-hour assays in a low-nutrient assay medium with three-days-old biofilms was 3.9 ± 2.0 ∙ 10-14 L ∙ cell–1 ∙ h–1, which is three to five times lower than the rates found in assays with planktonic cultures of G. sulfurreducens in this and previous studies. The fraction of MeHg of total Hg within the biofilms was, however, remarkably high (close to 50 %), and medium/biofilm partitioning of inorganic Hg (Hg(II)) indicated low accumulation of Hg(II) in biofilms. These findings suggest a high Hg(II) methylation capacity of G. sulfurreducens biofilms and that Hg(II) transfer to the biofilm is the rate-limiting step for MeHg formation in this system.